Old Cricket - Wheeler, Lisa; 1963-; Goembel, Ponder (New York, 2003)
Old Cricket doesn't feel like helping his wife and neighbors to prepare for winter and so he pretends to have all sorts of ailments that require the doctor's care, but hungry Old Crow has other ideas.
Keywords: Helpfulness; Crickets; Fiction; Crows; Fiction; Fiction; Behavior; Fiction